On (Dis) connections and transformations: The role of the agricultural innovation system in the adoption of improved forages in Colombia - Enciso, Karen; Triana Ángel, Natalia; Díaz, Manuel Francisco; Burkart, Stefan (Frontiers Media, 2022)
Feeding improvement strategies are key in increasing cattle productivity and reducing its environmental footprint. Nevertheless, Colombian tropical cattle systems still feature serious deficiencies in both forage quality and availability. As a result of past and ongoing forage Research and Development (R&D) processes, institutions have released 23 grass and legume cultivars of superior characteristics in terms of forage quality, supply, or adaptation to different soil and climate conditions, while providing numerous environmental benefits. However, low levels of adoption are observed: although R&D processes are a necessary condition for adoption, they are still not sufficient to guarantee agricultural technification in Colombia. The ultimate success occurs only when endusers make effective use of a technology–a link constantly interrupted. Agricultural innovation requires complex processes of interaction in which knowledge is shared amongst organizations involved in the Agricultural Innovation System (AIS), namely: suitable links, attitudes, practices, governance structures, and policies. The objective of this study is to identify limitations and opportunities in R&D, adoption, and diffusion of forage technologies in Colombia from an AIS perspective. Particularly, we present a study case pertaining to research institutions only, to (a) map the involved actors and describe their roles and links, and (b) identify the events that marked the evolution of the AIS and the course of forage R&D in its research-related components. We applied a qualitativemethodology based on focus group discussions, in-depth interviews, literature review, and historical analysis. Results show that the complex nature of institutions and the interactions between them determine the historical transformation of diffusion of forage technologies. The lack of connection between institutions and the weak intensity of the relationships, prevent the convergence of interests and objectives, leading to vicious cycles that hamper technology adoption. Insufficient synchronization between institutions of different nature (and even between those that share similar objectives) results in efficiency losses due to an unnecessary repetition of activities and processes. We provide recommendations for policy- and decision-makers that will help in both a restructuration of the AIS and a better allocation of funds for R&D, and thus support the development of more effective pathways for forage adoption and scaling.